2020
DOI: 10.1002/ecs2.3073
|View full text |Cite
|
Sign up to set email alerts
|

Host plant resistance promotes a secondary pest population

Abstract: Insecticides can cause secondary pest outbreaks that weaken the benefit of chemical pest control. These detrimental nontarget effects motivate the use of alternative pest management strategies such as host plant resistance and intercropping. However, when alternative pest management strategies effectively suppress primary pests, they also have the potential to promote secondary pest populations via competitive release. The potato leafhopper (Empoasca fabae) is a key pest of alfalfa, and leafhopper-resistant cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…However, it is possible that non‐target insect pests are indirectly influenced. This was shown recently for pea aphid ( Acyrthosiphon pisum ), which was at least partly promoted by release from potato leafhopper ( Empoasca fabae ) competition due to insecticide application (Straub et al, 2020), and this indirect effect is also applicable to Bt‐crops (Zeilinger et al, 2016). The latter authors have reported a competitive release and outbreak of non‐target pests in transgenic Bt‐cotton.…”
Section: Insect Pest Resistance Breeding Approachesmentioning
confidence: 76%
“…However, it is possible that non‐target insect pests are indirectly influenced. This was shown recently for pea aphid ( Acyrthosiphon pisum ), which was at least partly promoted by release from potato leafhopper ( Empoasca fabae ) competition due to insecticide application (Straub et al, 2020), and this indirect effect is also applicable to Bt‐crops (Zeilinger et al, 2016). The latter authors have reported a competitive release and outbreak of non‐target pests in transgenic Bt‐cotton.…”
Section: Insect Pest Resistance Breeding Approachesmentioning
confidence: 76%
“…ervi parasitoids, and ladybug predators (Coccinellidae) – two insect groups from a diverse community of alfalfa‐associated arthropods that were emphasized due to their large impacts on pea aphids. We also made counts of potato leafhoppers, potential pea aphid competitors (e.g., Straub et al, 2020), that trigger “hopperburn” damage on alfalfa plants.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to counts of pea aphids (winged and unwinged), we also censused A. ervi parasitoids , ladybug predators (Coccinellidae), and potato leafhoppers ( Empoasca fabae ). The former two insects are large sources of pea aphid mortality that may be thwarted by facultative symbionts [ 98 , 99 ], while the latter is a potential competitor of the pea aphid, e.g., [ 100 ]. Insect counts, climate data, and mortality assay data (below) can be found in Table S2 .…”
Section: Methodsmentioning
confidence: 99%